2017
DOI: 10.1200/jgo.2016.003392
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mutational Status and Brain Metastases in Non–Small-Cell Lung Cancer

Abstract: IntroductionEpidermal growth factor receptor (EGFR) mutations in non–small-cell lung cancers (NSCLC) may be more common in patients with brain metastases. Previous studies, however, did not adjust for effects of confounding variables.MethodsThis retrospective study included 1,522 consecutive patients with NSCLC, whose tumors were diagnosed and tested for EGFR mutations at the University of Nebraska Medical Center (Omaha, NE) and Tata Memorial Hospital (Mumbai, India). Multivariate logistic regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…However, this study had small sample sizes, which may have limitations. In 2016, a retrospective study including 1522 consecutive NSCLC patients reported that patients with EGFR mutations at the time of diagnosis have a nearly twofold higher risk of brain metastases . The results above suggest that the EGFR mutation status could have an influence on the CNS progression of NSCLC.…”
Section: Oncogenementioning
confidence: 97%
“…However, this study had small sample sizes, which may have limitations. In 2016, a retrospective study including 1522 consecutive NSCLC patients reported that patients with EGFR mutations at the time of diagnosis have a nearly twofold higher risk of brain metastases . The results above suggest that the EGFR mutation status could have an influence on the CNS progression of NSCLC.…”
Section: Oncogenementioning
confidence: 97%
“…The frequency and distribution of these mutations quite variable across the globe. EGFR mutations occur at a much higher rate in adenocarcinoma in East Asia than in the United States and Europe and are also more common in women than men . However, the frequency of other mutations ( ERBB2 , RET , BRAF , ROS1) are similar among Asian and white populations .…”
Section: Introductionmentioning
confidence: 98%
“…While the treatment of lung cancer follows the same principles around the world, the differences in the epidemiology of lung cancer and the genetic variations in the patients lead to some variations in the exact treatments received by patients. As a result, since an increased proportion of patients in Asia have activating EGFR mutations, there is an increased prevalence in the use of EGFR tyrosine kinase inhibitors in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high heterogeneity, analyses stratified by study design ( Figure 2D) suggested that association was significant between EGFR mutations and the incidence of BMs in cohort (16)(17)(18)(19)(25)(26)(27)(28)(29)(30)(31)(36)(37)(38)(39)(40)(41)(42) (P=0.381, I 2 =6.1%) ( Figure 3A). Patients with EGFR mutations were more susceptible to BMs than wild type cases either in adenocarcinoma patients (OR =1.93; 95% CI, 1.59-2.35; P=0.000) or in advanced (stage IV) NSCLC patients (OR =1.83; 95% CI, 1.43-2.36; P=0.000).…”
Section: Incidence Of Bmsmentioning
confidence: 99%
“…The NOS was used to perform quality assessment on all 22 studies and 14 (17,18,(25)(26)(27)(28)30,(32)(33)(34)(35)(36)38,42) high-quality and 8 (16,19,29,31,37,(39)(40)(41) as low-quality.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%